2017
DOI: 10.1097/sle.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Does Sugammadex Administration Affect Postoperative Nausea and Vomiting After Laparoscopic Cholecystectomy: A Prospective, Double-Blind, Randomized Study

Abstract: Sugammadex seems to be effective in decreasing the incidence of PONV, severity of nausea, number of patients who suffered from nausea and vomiting, and need for rescue antiemetic, although there were no significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
7
1
1
Order By: Relevance
“…Our other secondary outcomes were chosen because of previous literature that has been published comparing use of SUG to neostigmine combined with an anticholinergic agent in regard to postoperative complications, especially PONV and RNMB. Whereas our study found no difference between the groups for PONV reported within 24 hours of surgery, a prospective, randomized trial conducted by Tuna et al 15 in laparoscopic cholecystectomy patients reported PONV incidence of 60% in the SUG group versus 77% in the neostigmine/atropine group, although the difference was not found to be statistically significant. A large retrospective study looking at 1444 patients found that reversal with SUG compared with NG was associated with the lowest rates of PONV ( P < 0.05) as well as potentially lower risks of adverse pulmonary outcomes postoperatively.…”
Section: Discussioncontrasting
confidence: 97%
“…Our other secondary outcomes were chosen because of previous literature that has been published comparing use of SUG to neostigmine combined with an anticholinergic agent in regard to postoperative complications, especially PONV and RNMB. Whereas our study found no difference between the groups for PONV reported within 24 hours of surgery, a prospective, randomized trial conducted by Tuna et al 15 in laparoscopic cholecystectomy patients reported PONV incidence of 60% in the SUG group versus 77% in the neostigmine/atropine group, although the difference was not found to be statistically significant. A large retrospective study looking at 1444 patients found that reversal with SUG compared with NG was associated with the lowest rates of PONV ( P < 0.05) as well as potentially lower risks of adverse pulmonary outcomes postoperatively.…”
Section: Discussioncontrasting
confidence: 97%
“…Tas Tuna et al . 443 confirmed these results in patients undergoing elective laparoscopic cholecystectomy surgery. PONV prophylaxis is rarely warranted in low-risk patients.…”
Section: Summary Of Current Recommendations For Reducing the Risk Of supporting
confidence: 66%
“…It has been established that an increase in surgery duration may increase the incidence of PONV whereby each 30-min increase in duration increases PONV risk by 60%, so that a baseline risk of 10% is increased to 16% after 30 min ( 22 ). Tas Tuna et al ( 23 ) reported no significant difference in the incidence of PONV at all time intervals between patients receiving neostigmine 40 μg /kg (with atropine) vs. patients receiving sugammadex 2 mg/kg undergoing laparoscopic cholecystectomy ( 24 ). In their study, none of their patients received antiemetic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%